2020
DOI: 10.1371/journal.pone.0237766
|View full text |Cite
|
Sign up to set email alerts
|

Semen parameters and fertility potency of a cloned water buffalo (Bubalus bubalis) bull produced from a semen-derived epithelial cell

Abstract: Semen contains epithelial cells that can be cultured in vitro . For somatic cell nuclear transfer applications, it is essential to know whether clone(s) produced from semen-derived epithelial cells (SedECs) are healthy and reproductively competent. In this study, the semen and fertility profile of a cloned bull (C1) that was produced from a SedEC were compared with its donor (D1) and with two cloned bulls (C2, C3) that were produced from commonly used skin-derived fibroblast cells (SkdFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Many researchers have reported that the cleavage rate in the first 24 hours can be considered as the fertilization rate (Beck-Fruchter et al, 2014;Saini et al, 2020) in scientific reports. It was also reported that the IVF rate is lower in buffaloes (45%-50%) compared to cattle (70%) (Sales et al, 2015) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that the cleavage rate in the first 24 hours can be considered as the fertilization rate (Beck-Fruchter et al, 2014;Saini et al, 2020) in scientific reports. It was also reported that the IVF rate is lower in buffaloes (45%-50%) compared to cattle (70%) (Sales et al, 2015) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fresh semen, as well as frozen and thawed semen, can be used in the IVF process (Duran et al, 2017;Rubessa et al, 2019). Numerous methods are available for preparing sperm for IVF (Parrish, 2014;Romar et al, 2016;Saini et al, 2020;Volpes et al, 2016). One of the most common mediums used for the processing of semen is the solution of Brackett & Oliphant (BO) (Akter et al, 2023;Smetanina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The overall average pregnancy (%) in buffaloes was found 43.55±4.90 when AI was conducted in estrous synchronized buffalo (kumar et al 2016). The non-return rate following AI using frozen-thawed semen from cloned buffalo bull was found 46-50% (Saini et al 2020). Conception is the nal destination of ejaculated sperm and ovulated oocytes that largely deepens on semen quality, insemination technique, proper timing of AI and other management and environmental (Dalton et al 2010).…”
Section: Sperm Kinematicsmentioning
confidence: 99%
“…Another group of researchers conducted research using antioxidant micronutrient supplementation in Murrah buffalo, enhancing udder health and milk production [21]. Semen parameter and fertility potency were performed using cloned water buffalo (Bubalus bubalis) in a study [22]. Moreover, various researches were done in India about the effect of progesterone on water buffalo, identification and characterization of traitspecific SNPs using ddRAD sequencing in water buffalo, nanotechnological application in buffalo, etc.…”
Section: Background Of Buffalo Research In the Asian Subcontinentmentioning
confidence: 99%